2017
DOI: 10.5194/isprs-annals-iv-4-w5-33-2017
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic and Geometric Reasoning for Indoor Building Models With Electric Installations – Bridging the Gap Between Gis and Bim

Abstract: ABSTRACT:3D city and building models according to CityGML encode the geometry, represent the structure and model semantically relevant building parts such as doors, windows and balconies. Building information models support the building design, construction and the facility management. In contrast to CityGML, they include also objects which cannot be observed from the outside. The three dimensional indoor models characterize a missing link between both worlds. Their derivation, however, is expensive. The seman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…The interested reader is also referred to the study conducted by Pintore et al (2020) which provides an overview on input sources, the structure of output models and a possible reconstruction pipeline as well as future research trends. Dehbi et al (2017) suggested a stochastic approach to obtain a model from sparse observations rather than relying on conducting intensive surveying overhead.…”
Section: Related Workmentioning
confidence: 99%
“…The interested reader is also referred to the study conducted by Pintore et al (2020) which provides an overview on input sources, the structure of output models and a possible reconstruction pipeline as well as future research trends. Dehbi et al (2017) suggested a stochastic approach to obtain a model from sparse observations rather than relying on conducting intensive surveying overhead.…”
Section: Related Workmentioning
confidence: 99%